Propuesta de una arquitectura empresarial para una empresa de transporte terrestre de pasajeros (2015)
"For some time now Colombia has had great problems with the urban and rural transport system, which significantly affects the quality of life of the inhabitants of a certain sector in particular, public transportation in Colombia is considered inefficient, unsafe, polluting, among others. The streets of Colombian cities and intermunicipal road corridors are populated by obsolete buses that functioned without taking into account the public safety, pollution and public order of the city, and over time they migrated to integrated transport systems such as Transmilenio and the SITP, which initially worked in a moderately acceptable manner but unfortunately, over time, the great population growth that the city and surrounding villages of the Bogota savanna would have was not contemplated, this increase in demand had to go from hand with the growth of the transportation system, which unfortunately did not happen, and what that initially was contemplated as the solution of the century, now is no more, than a system destined to failure like its predecessors ... "- Extract of the document